Reconstruction of the Waqf Pledge as a Juridical Acronym for Expert Waqf Dispute Resolution - Achmad Yani (Management of Zakat and Waqf Journal (MAZAWA), 2023)
productive waqf management can contribute to the economy of the poor. Waqf land that is managed as a business enterprise, in various countries, is able to contribute to the state's income to the level of urgency. However, after waqf land becomes productive, a problematic phenomenon often arises; the phenomenon of claiming ownership of waqf land by the heirs of the waqif. As a result, productive waqf land becomes disputed and harms many people. This research provides a solution to this problem through the reconstruction of expert waqf into normative regulations. This research is a literature study, where the researcher emphasizes on normative analysis for acronym regulation. However, the sample is taken from the results of field research. This research is desk-based with qualitative data, qualitative supported by secondary data from interview and documentary field research. The analysis is conducted on running content. The findings show two things; first, the social reconstruction of expert waqf is carried out in three forms; 1) the principle of mutual trust and kinship in the implementation of expert waqf is witnessed by two family members; 2) handing over waqf in front of the village government or customary tribe. 3) the land endowed to the nadzir has the consent of the successor heirs. Second, the reconstruction of the legislative acronym is formed on five things; 1) the waqf pledge deed gets a recommendation from the head of the local government as a strong document of the AIW; 2) individual or corporate nadzirs are determined by social figures who understand the procedures for waqf management and administration; 3) mauquf alaih witnesses the waqf between the waqif and nadzir; 4) expert waqf is intended for public welfare, witnessed by the nasab guardian; 5) expert waqf that has passed away is automatically transferred to waqf khairi.